The Importance of Indonesia’s Nationalism Revitalization in the Globalization Era: A Historical Perspective - Singgih Tri Sulistiyono (Diponegoro University, 2018)
This article analyze on how nationalism which is product of nineteenth century in Europe can be revitalized in facing the challenge of globalization. In Indonesian context, this issue is very urgent to be discussed considering the fact that the process of globalization tends to be confronted with the spirit of nationalism. Sometime nationalism is viewed as an obsolete tradition that should be revitalized. But there are still many people who believe that nationalism is still indispensable in the face of an increasing wave of globalization. However nationalism must be revitalized in order to be able to face the challenge of globalization.For this purpose, it is very interesting to strengthen the spirit of nationalism by revitalizing it for improving the nation competitiveness in facing the expansion of globalization. The questions are in what wayscouldnationalismbe revitalizedinorder to improve thenationcompetitivenesstoface theglobal competition?In addition, the fundamentalquestionto be askediswhydoes Indonesiannationalismneed to be revitalized? What is wrongwithIndonesiannationalism?IfIndonesiannationalismcan berevitalized, howis it done?Those are set of questionsthatwill bediscussedin thispaper.